Impaired Proximal Esophageal Contractility Predicts Pharyngeal Reflux in Patients With Laryngopharyngeal Reflux Symptoms. Issue 10 (1st October 2021) - Sikavi, Daniel R.; Cai, Jennifer X.; Leung, Ryan; Carroll, Thomas L.; Chan, Walter W.
Abstract : OBJECTIVES: The pathophysiology of laryngopharyngeal reflux (LPR) remains incompletely understood. Proximal esophageal motor dysfunction may impair bolus clearance, increasing the risk of pharyngeal refluxate exposure. We aimed to evaluate the association of proximal esophageal contractility with objective reflux metrics. METHODS: We evaluated adults with LPR symptoms undergoing high-resolution manometry (HRM) and combined hypopharyngeal-esophageal multichannel intraluminal impedance-pH testing at a tertiary center between March 2018 and August 2019. Routine parameters per Chicago classification were obtained on HRM. Proximal esophageal contractility was evaluated using proximal contractile integral (PCI), which quantifies contractile pressure >20 mm Hg for the region spanning the distal margin of the upper esophageal sphincter and transition zone. Univariate (Kendall correlation and Student t test) and multivariable (general linear regression and logistic regression) analyses were performed. RESULTS: We enrolled 138 patients (66.7% women, mean age 57.1 years) in this study. Lower PCI was associated with an elevated risk of increased pharyngeal reflux (adjusted odds ratio 0.83 per 100 mm Hg-s-cm change in PCI, 95% confidence interval: 0.69–0.98), with a trend toward increased bolus exposure time and total reflux events, after multivariable adjustment. The relationship between PCI and pharyngeal reflux was strongest among participants without a primary motility disorder on HRM (adjusted odds ratio 0.63, 95% confidence interval: 0.42–0.85, P interaction = 0.04). Among continuously expressed reflux parameters, lower PCI was significantly associated with more distal acid reflux events (β = −0.0094, P = 0.03) and total reflux events (β = −0.0172, P = 0.05), after adjusting for confounders. DISCUSSION: Reduced proximal esophageal contractility as assessed by decreased PCI on HRM independently predicted increased pharyngeal reflux in patients with LPR symptoms, particularly among those without a coexisting motility disorder.